Impact of Cattle Grazing on Selected Environmental Variables in Pasture-Based Livestock Production System - Ajorlo, Majid (2010)
Livestock production system has been developed to meet the increasing demand for ruminant products in Malaysia, however, few studies have focused on the assessment of the impact of such production system on the environmental variables such as soil, vegetation and surface water. With increasing demand for livestock products which resulted in the development of livestock production system, quantification and understanding of the environmental impacts of livestock production are necessary prerequisites for any effective planning to enhance environmental quality. This study aims to assess the impacts of short-term (2-year) heavy and long-term (33-year) moderate grazing by cattle on the quality of soil, vegetation and surface water in communal native and commercial improved tropical pasture ecosystem at both the farm and catchment scales. The study was conducted at the Universiti Putra Malaysia Livestock Section, about 20 km south of Kuala Lumpur, Malaysia. Two study sites, the Ladang 2 farm (3º 00’ 28"N; 101º 42’ 10"E) and the TPU catchment (2º 58' 53"N; 101º 43' 38"E), represented a native and improved pastures, respectively. Water samples from a year-round monitoring of streams in the pastures with cattle grazing and ungrazed exclosure were analyzed for water quality parameters of EC, DO, pH, NH3-N, COD, TSS, Fecal Coliform (FC), and E. coli. Soil chemical characteristics such as pH, EC, OC, TN, AP, exchangeable cations, and heavy metals (Cd, Pb, Cu, Cr, Fe, Zn, and Mn) were analyzed. Infiltration rate, bulk density, penetration resistance, moisture content and porosity were determined to assess alterations in soil physical properties. A combination of both systematic and randomized method was used to measure pasture vegetation and invasive species. Root morphological and distribution characteristics were measured using soil coring approach. Water quality data were analyzed with the multivariate analysis of variance, multivariate statistical techniques and the Harkins’ index. Soil chemical and physical properties and root morphological data were analyzed with the repeated measures analysis of variance. The multivariate analysis of variance was used to analyze pasture vegetation and invasive species data. The results showed that the streams of the TPU catchment were classified as classes II and I in the grazed and ungrazed pastures, respectively. Streams in both the grazed and ungrazed sites were classified as class II in ‘Ladang 2’ farm. Significant difference between the grazed and ungrazed treatments was observed for water quality variables of TSS, COD and FC at the Ladang 2 farm. DO, BOD, pH, EC, TSS, COD, NH3-N, FC and E. coli varied significantly between the grazed and ungrazed pasture in the TPU catchment. The study also revealed that the moderate grazing led to higher soil pH, EC, AP and Mg+2 and lower TN, OC, Ca+2 and K+ at the improved pasture. Higher levels of pH, EC, OC and lower concentrations of AP, TN, Ca+2 and Mg+2 were observed at the native pasture. Moderate grazing had significant effect on heavy metal concentrations in soils, but heavy grazing did not lead to a significant accumulation of heavy metals in the soils. Contrary to the heavy grazing, moderate grazing had no negative impacts on soil physical properties. Moderate grazing increased grasses regrowth rate and herbage mass yield; while heavy grazing had no significant effect on those characteristics. Moderate grazing affected the invasive species population adversely; however heavy grazing provided relatively desirable condition for their establishment and infestation. Mean root diameter, surface area and volume densities were not affected by moderate grazing in the improved pasture. However, root surface area and mass densities were affected at heavily grazed native pasture. Grass roots were significantly affected by heavy grazing at native pasture, but unaffected by moderate grazing at the improved pasture. The results indicated that cattle grazing affect the surface water in pasture ecosystem adversely. Cattle grazing effects on soil chemical characteristics depend on the type of elements, which may increase or decrease over time. Soil heavy metals content can increase in pastures where cattle have been grazing for a long-term. Moderate grazing can influence pasture production positively and decrease the invasive species. Pasture plant roots were not adversely affected by either short-term heavy or long-term moderate grazing intensities. Keywords: Water quality, Vegetation cover, Invasive species, Root morphology, Soil chemical properties, Soil physical properties, Heavy grazing, Moderate grazing